2000
DOI: 10.1089/104454900314627
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Hydrogen Peroxide-Generating Enzyme Fatty Acyl CoA Oxidase Activates NF-kappa B

Abstract: Peroxisome proliferators are a class of hepatic carcinogens in rodents and have been proposed to act in part by increasing oxidative stress. Fatty acyl CoA oxidase (FAO), which is highly induced by peroxisome proliferators, is the hydrogen peroxide-generating enzyme of the peroxisomal beta-oxidation pathway. We previously showed that the treatment of rats and mice with the peroxisome proliferator ciprofibrate resulted in increased hepatic NF-kappaB activity and suggested that this effect may be secondary to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 37 publications
2
37
0
Order By: Relevance
“…The antioxidants vitamin E and catalase inhibited this activation (28). Conversely, specific inhibition of catalase resulted in peroxisome-derived oxidative imbalance, which rapidly impaired mitochondrial function and caused mitochondrial damage (29).…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidants vitamin E and catalase inhibited this activation (28). Conversely, specific inhibition of catalase resulted in peroxisome-derived oxidative imbalance, which rapidly impaired mitochondrial function and caused mitochondrial damage (29).…”
Section: Discussionmentioning
confidence: 99%
“…This cell line has previously been shown to support reporter gene expression for a PKC-dependent promoter that included an AP-1 site (7), and is known to express NF-B (21,22). Moreover, it does not express CXCR2 and normally does not respond to known ligands for KSHV-GPCR.…”
Section: Kshv-gpcr Constitutively Induces Proinflammatory Transcriptimentioning
confidence: 99%
“…Preoxisomal acyl-CoA oxidase 1 (ACOX1) is the first and rate-limiting enzyme in the peroxisomal beta-oxidation pathway catalysing the desaturation of acylCoAs to 2-trans-enoyl-CoAs, thereby producing H 2 O 2 (Fournier et al, 1994;Li et al, 2000). Fan et al (1998) found that homozygous ACOX1-null mice were viable, but growth-retarded and infertile.…”
Section: Introductionmentioning
confidence: 99%